Peran Kredibilitas dan Reputasi Digital dalam Meningkatkan Kinerja Keuangan Hotel Bagus Jaya Ambarawa - Alia Sri Nawani; Tri Maryani (Mahesa Research Center, 2026)
This article aims to analyze and understand the role of digital credibility and digital reputation in improving the financial performance of Hotel Bagus Jaya Ambarawa. The problem focuses on how the management of credible digital information and online reputation formed through customer reviews contributes to revenue growth, occupancy rates, and cash flow stability in small-scale hotels. To address this issue, this study adopts the theoretical perspectives of intangible assets and signaling theory, which view reputation and trust as sources of long-term economic value. Data were collected through in-depth interviews, observation, and documentation involving internal hotel informants, including the owner or manager, finance or operational staff, front office staff, and digital media administrators, and were analyzed qualitatively using a thematic approach. The findings indicate that digital credibility, reflected in the accuracy and consistency of hotel information, is able to build consumer trust and encourage increased bookings. A positive digital reputation plays a role in attracting new guests, maintaining revenue stability, and providing flexibility in room pricing strategies. This study concludes that digital credibility and digital reputation are strategic assets that play an important role in supporting the financial performance and business sustainability of small-scale hotels.